2010
DOI: 10.1590/s0365-05962010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Imunoglobulina intravenosa para tratamento de epidermólise bolhosa adquirida grave refratária a terapia imunossupressora convencional

Abstract: Acquired bullous epidermolysis is a chronic and rare bullous subepidermal disease. It usually begins in adulthood and its etiology is unknown although it is associated with antibodies against type VII collagen. There are spontaneous and trauma induced formation of blisters that may cause serious complications. Treatment is disappointing and difficult. Apart from conventional therapy with systemic corticosteroid, new therapeutic modalities such as intravenous immunoglobulin are currently being used. This report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As for the acquired form, it was verified that it is a disease that starts in adulthood, regardless of race or gender, however, it usually settles in adulthood (higher incidence at 50 years of age), being related to the HLA-DR2 allele ( MOSQUEIRA, 2010). Accordingly, the study by Silva (2020) revealed that people with this phenotype are more susceptible to the deposit of IgG and C3 in the basement membrane (occasionally IgA and IgM are also present).…”
Section: Discussionmentioning
confidence: 99%
“…As for the acquired form, it was verified that it is a disease that starts in adulthood, regardless of race or gender, however, it usually settles in adulthood (higher incidence at 50 years of age), being related to the HLA-DR2 allele ( MOSQUEIRA, 2010). Accordingly, the study by Silva (2020) revealed that people with this phenotype are more susceptible to the deposit of IgG and C3 in the basement membrane (occasionally IgA and IgM are also present).…”
Section: Discussionmentioning
confidence: 99%
“…IVIG modulates the autoimmune response, reducing and neutralizing antibodies. 117 It is usually administered at 2g/kg/ cycle over 3 to 5 days as monotherapy or in combination with other drugs, such as systemic corticosteroid and dapsone, with good response in patients with recalcitrant disease. 103,117 One long-term study evaluated 10 patients with EBA that were resistant to conventional therapy after IVIG administration, resulting in a satisfactory response in all cases.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%
“…117 It is usually administered at 2g/kg/ cycle over 3 to 5 days as monotherapy or in combination with other drugs, such as systemic corticosteroid and dapsone, with good response in patients with recalcitrant disease. 103,117 One long-term study evaluated 10 patients with EBA that were resistant to conventional therapy after IVIG administration, resulting in a satisfactory response in all cases. 118 Patients received 16-31 IVIG cycles over 30-52 months, allowing adjuvant medications (prednisone, dapsone, and others) and, later, IVIG to be withdrawn.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%